2020
DOI: 10.1002/cmdc.202000438
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Generation Meridianin Analogues Inhibit the Formation of Mycobacterium smegmatis Biofilms and Sensitize Polymyxin‐Resistant Gram‐Negative Bacteria to Colistin

Abstract: Drug‐resistant bacteria are rapidly becoming a significant problem across the globe. One element that factors into this crisis is the role played by bacterial biofilms in the recalcitrance of some infections to the effects of conventional antibiotics. Bacteria within a biofilm are highly tolerant of both antibiotic treatment and host immune responses. Biofilms are implicated in many chronic infections, including tuberculosis, in which they can act as bacterial reservoirs, requiring an arduous antibiotic regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“… 18 , 19 Additionally, brominated derivatives of the kinase inhibitor meridianin D, which bears structural similarity to carbazoles, have been shown to inhibit biofilm formation in MRSA. 20 , 21 An evaluation of regulatory kinases in S. aureus suggested that the PASTA kinase Stk1 could be the molecular target of the lead carbazoles. Stk1 is a global regulator of cell-wall homeostasis and biofilm formation and has been implicated in the regulation of resistance to β-lactams and vancomycin.…”
mentioning
confidence: 99%
“… 18 , 19 Additionally, brominated derivatives of the kinase inhibitor meridianin D, which bears structural similarity to carbazoles, have been shown to inhibit biofilm formation in MRSA. 20 , 21 An evaluation of regulatory kinases in S. aureus suggested that the PASTA kinase Stk1 could be the molecular target of the lead carbazoles. Stk1 is a global regulator of cell-wall homeostasis and biofilm formation and has been implicated in the regulation of resistance to β-lactams and vancomycin.…”
mentioning
confidence: 99%
“…The Melander group recently reported the synthesis and evaluation of indolylpyrimidine analogs of meridianin D that potentiate colistin in Gram-negative bacteria (Huggins et al, 2018;Zeiler et al, 2020). Meridianin D (50, Figure 5), which is structurally related to the pyrazolopyridazines described above, was isolated from a marine invertebrate and has been previously reported as a kinase inhibitor (Franco et al, 1998;Giraud et al, 2011;Gompel et al, 2004).…”
Section: Kinase Inhibitors As Antibiotic Adjuvantsmentioning
confidence: 99%
“…Analog 51 displayed enhanced potentiation, lowering the colistin MIC 512-fold in both A. baumannii 4106 and K. pneumoniae B9 (Figure 5). Second-generation analogs further elaborated the structure-activity relationship and provided additional analogs (52, 53, Figure 5) with phenyl groups that showed comparable colistin potentiation as 51 in A. baumannii and K. pneumoniae (Zeiler et al, 2020). Additionally, 52 was able to lower the MIC of colistin to the resistance breakpoint at a concentration of only 5 μM, indicating that this analog has improved potency and activity of the previous lead analog, 51, which required at least 10 μM dosing to achieve similar results.…”
Section: Kinase Inhibitors As Antibiotic Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the premise that agents capable of inhibiting M. abscessus biofilm formation and/or of dispersing established M. abscessus biofilms may potentiate the activity of antibiotics used in combination, our attention turned to 2-aminoimidazoles (2-AI). The decision to study 2-AIs was based upon previous studies by the Melander laboratory and others that showed that the 2-AI class of small molecules and related scaffolds (2-aminopyrimidines (2-AP), 2-aminobenzimidazoles (2-ABI), 2-aminoquinazolines and 2-AI-containing meridianin analogs) display broad-spectrum biofilm inhibition and dispersion activity against Gram-negative and Gram-positive bacteria, including Mycobacterium tuberculosis and the nontuberculous Mycobacterium species, M. smegmatis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Importantly, some 2-AI and 2-ABI compounds demonstrated the ability to sensitize M. tuberculosis and M. smegmatis to isoniazid, rifampicin and β-lactams [ 15 , 19 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%